THE COLLECTION OF MANUSCRIPTS FROM THE NOUL-NEAMŢ MONASTERY - Stela GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
The new monastery, called “The New Neamţ” (Romanian: “Noul Neamţ”), established in 1864 by the monks who had left the old Neamţ community, took over not only the name of the oldest and richest monastic foundation in Moldova, but also the secular traditions of this important cultural center. The monastery’s abbot, Teophan Cristea, adopted both the traditions and the institution previously founded here by Saint Paisius from Neamţ. The Neamţ monks brought with them numerous precious manuscripts, documents and old Romanian books, which they also protected in this new location.